KEPENTINGAN NASIONAL INDIA DALAM SHANGHAI COOPERATION ORGANIZATION (SCO) - Risa Aprilia Agnesalamah (Global Political Studies Journal, 2017)
The limited access and capability of India as an observer makes India want accession to become a full member of the Shanghai Cooperation Organization (SCO) as an effort to fulfill its national interests. This study aims to describe India's national interests in SCO membership and obstacles it faces. The research method used is qualitative. The results of this study indicate that economic interests, security, energy and connectivity are India's motivation to join SCO membership. India views SCO as an arena to achieve its national interests. These interests include building economic cooperation, combating terrorism and radicalism, joining regional anti-terrorist structures, combating narcotics trafficking, and fulfillment of energy needs. The obstacles for India in the membership of SCO is India’s limited capability due to China’s domination in the organization and there is a difference understanding of terrorists between India and SCO.